Aplicaciones biotecnológicas del desarrollo in vitro de folículos bovinos obtenidos de ovarios fetales o prepúberes (1999)
ABSTRACT: During the present decade the protocols for in vitro maturation (IVM), in vitro fertilization (IVF) and in vitro development (IVD), have been developed in our country. The first report on in vitro rat folliculogenesis was published in 1996. Our group was encouraged to initiate the procedure for standardize the model of bovine folliculogenesis in vitro by using fetal bovine ovaries, with the aim to contribute to develop biotechnological alternatives for animal reproduction, and to have a model in vitro in which medical compounds with potential use in animal reproduction could be evaluated, previous to its application in in vivo studies. In this paper we present a critical review about the information concerning the field of bovine in vitro follicular development; in addition, some areas of research are proposed in which model could be useful for basic and clinical research.